Synthesis of Some New N-Thio Carbamoyl-3-Methyl-4[2’-{4’-p-subst./unsubst.)-phenyl}thiazolyl hydrazono]-2-Pyrazolin-5-one with Possible Antibacterial Activity - Singh Rawat, Bhupender; Mehra, S.C. (Asian Journal of Chemistry, 2012)
Several new N-thio carbamoyl-3-methyl-4-[2’-{4’-p-subst./unsubst.)-phenyl}thiazolyl hydrazono]-2-pyrazolin-5-one (II) have been prepared by reaction of ethyl-2-(2’-aryl hydrazono)-3-oxo-butyrate (I) with thiosemicarbazide in ethylacetoacetate All these synthesized pyrazolines have been screened against a few micro-organisms for antibacterial activity. Compounds were characterized by infrared and NMR spectra.